Effectiveness of a web-based intervention in reducing binge drinking among nightclub patrons - Yago C Baldin; Adriana Sanudo; Zila M Sanchez (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To evaluate the effectiveness of a web-based intervention in reducing binge drinking among nightclub patrons after six months. METHODS We carried out a website survey with probabilistic sample in 31 nightclubs in the city of São Paulo, Brazil, which originated a randomized controlled trial with 1,057 participants. Those classified as problem drinkers (n = 465) using the Alcohol Use Disorders Identification Test were randomized into two study groups - intervention and control. The web-based intervention consisted of exposing the participants to a normative feedback screen about their alcohol consumption, characterizing the risks associated with amount consumed, money spent on drinks, drinking and driving, risk classification of Alcohol Use Disorders Identification Test, and tips to reduce damage. RESULTS There was a significant reduction in the practice of binge drinking in the week estimated at 38% among participants in the intervention group after six months (p < 0.05). However, there was no significant reduction in the outcomes when we analyzed the intervention and control groups and at baseline and after sixth months, simultaneously. CONCLUSIONS We cannot conclude that digital tools reduce the pattern of binge drinking among party goers in São Paulo. More studies are needed with this methodology because of its attractiveness to this type of group, given the privacy and speed that personalized information is transmitted.